2004
DOI: 10.1002/ijc.20134
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of XPA, ERCC1 and XPF DNA repair proteins in testis tumor cell lines

Abstract: Over 80% of patients with advanced metastatic testis tumors can be cured using cisplatin-based combination chemotherapy. This is unusual as metastatic cancer in adults is usually incurable. Cell lines derived from testis tumors retain sensitivity to cisplatin in vitro. We previously investigated 2 testis tumor cell lines with a low capacity to remove cisplatininduced DNA damage and found that they had low levels of the DNA nucleotide excision repair proteins XPA, ERCC1 and XPF. To determine whether low levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(157 citation statements)
references
References 56 publications
6
149
1
1
Order By: Relevance
“…Ovarian cancer lines that developed resistance after exposure to cisplatin in vitro were found to have increased ERCC1 levels (Ferry et al, 2000). Most testicular cancer patients are cured by cisplatin (Bosl and Motzer, 1997) and most testicular cancer cell lines have low levels of ERCC1 and XPF (Koberle et al, 1997(Koberle et al, , 1999Welsh et al, 2004). Our data suggest that ERCC1 and XPF induction during cisplatin treatment contribute to the resistance of melanoma to chemotherapy.…”
Section: Discussionmentioning
confidence: 64%
“…Ovarian cancer lines that developed resistance after exposure to cisplatin in vitro were found to have increased ERCC1 levels (Ferry et al, 2000). Most testicular cancer patients are cured by cisplatin (Bosl and Motzer, 1997) and most testicular cancer cell lines have low levels of ERCC1 and XPF (Koberle et al, 1997(Koberle et al, , 1999Welsh et al, 2004). Our data suggest that ERCC1 and XPF induction during cisplatin treatment contribute to the resistance of melanoma to chemotherapy.…”
Section: Discussionmentioning
confidence: 64%
“…The expression levels of ERCC1 and XPF were normalized to RPA protein expression. RPA was chosen because it is a nuclear protein involved in several housekeeping aspects of DNA metabolism, and there was relatively little variation in RPA for cell lines from different tumor types (21).…”
Section: Methodsmentioning
confidence: 99%
“…Using in vitro models, it has been shown that testis tumor cell lines are characterized by reduced levels of ERCC1 and XPF compared to cell lines derived from other types of cancer (21). However, to date no data are available on the expression of ERCC1 and XPF in testicular tumors, although as mentioned above for non-seminomas cisplatin belongs to first-line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…We found that cellular protein extracts of a bladder cancer cell line were proficient for NER (Köberle et al, 1999). Furthermore, the core NER proteins are expressed to a similar extent in bladder cancer cell lines compared to normal non-cancerous cells (Köberle et al, 1999, Welsh et al, 2004. The removal of cisplatin induced DNA platination, which we previously observed in bladder cancer cell lines (Köberle et al, 1997), is therefore, at least in part, due to NER proficiency in these cells.…”
Section: Nucleotide Excision Repairmentioning
confidence: 50%